Effect of ballistic warm-up on isokinetic strength, balance, agility, flexibility and speed in elite freestyle wrestlers - Çetin, E.; Bulgay, C.; Çimen Polat, S.; Cicioglu, H. I.; Yarim, I. (Journal of Education and Training Studies, 2018)
The aim of this study is effect of ballistic warm-up on isokinetic strength, balance and some parameters in male elite freestyle wrestlers. 13 elite freestyle wrestlers at the age of 20.2±2.1 yrs, with 174.5±7.1 cm height and 81,67±15,36 kg weight participated in the study. Measurements were performed two different warm-up protocols. Running protocol at submaximal level on the treadmill for 10 minutes was applied for every wrestler. Ballistic Warm-up protocol involved 13 different movements for multi-muscle groups lasting for 10 minutes. Flexibility, speed, agility, balance, hand grip and isokinetic leg strength parameters were measured. Wilcoxon Signed Rank test was performed to find the difference between the protocols. Consequently, differences were found in flexibility, right hand grip strength, right posteromedial and posterolateral balance, left posteromedial and posterolateral balance, left and right hamstring and quadriceps strength parameters. Ballistic warm-up protocol can be more effective in many parameters, especially strength compared to ordinary warm-up.